International journal of multimedia data engineering and management - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
Recent advances in computing, networking, storage, and information technology have enabled the collection and distribution of vast amounts of multimedia data in a variety of applications such as entertainment, education, environmental protection, e-commerce, public safety, digital government, homeland security, and manufacturing. The proliferation of multimedia data and its rich semantics have created the needs for advanced techniques for in-depth content processing, analysis, indexing, learning, mining, searching, management, and retrieval. The International Journal of Multimedia Data Engineering and Management (IJMDEM) addresses the corresponding issues and challenges and publishes original research on new theories, algorithms, technologies, system design, and implementation in multimedia data engineering and management.
"An official publication of Information Resources Management Association."
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, no. 1 (Jan.-March 2010); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 1, no. 3 (2010).
Keywords: Database management -- Periodicals; Software engineering -- Periodicals; Expert systems (Computer science) -- Periodicals; Content-based retrieval; Image/video/audio databases; Learning support for multimedia data; Multimedia data engineering; Multimedia data indexing; Multimedia data mining; Multimedia data modeling; Multimedia data storage; Multimedia databases; Multimedia systems; Multimodal data analysis; Network support for multimedia data; New standards; Relevance feedback; Security support for multimedia data; Technologies and applications; Electronic books